2017
DOI: 10.1108/ijebr-07-2017-0216
|View full text |Cite
|
Sign up to set email alerts
|

Self-employment: the significance of ability, desire and opportunity

Abstract: Purpose The purpose of this paper is to examine the influence of ability, desire and opportunity on the individual’s intention to be self-employed. Design/methodology/approach The authors created a database from Swedish national registers consisting of all individuals residing in Sweden sometime during the period 1997-2010 and selected all 333,001 full sibling pairs, 12,810 maternal half sibling pairs and 15,944 paternal half sibling pairs. Three types of entrepreneurs were defined based on information from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…For example, recent advances in digital technologies have played a key role in growing a new, digital-based entrepreneurship and the development of related business models (Kraus et al , 2019; Nambisan, 2017). These technologies are having a disruptive impact on entrepreneurship, changing traditional patterns and helping discover new frontiers for entrepreneurs to explore (Broomé and Ohlsson, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For example, recent advances in digital technologies have played a key role in growing a new, digital-based entrepreneurship and the development of related business models (Kraus et al , 2019; Nambisan, 2017). These technologies are having a disruptive impact on entrepreneurship, changing traditional patterns and helping discover new frontiers for entrepreneurs to explore (Broomé and Ohlsson, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Digital technologies are having a disruptive impact on entrepreneurship and organizational strategies (Mazzei and Noble, 2017; Broome and Ohlsson, 2018; Keding, 2021). They include analytical tools, sharing platforms, the Internet of things, mobile devices and applications (Martin-Pena et al , 2018; Andriole, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…EIs are a representation of previously concealed latent potential (Broomé & Ohlsson, 2017) that act as a causal precursor to more observable individual actions (Dimov, 2007). Therefore, in the present context, EI is conveyed as a temporally embedded mindful willingness to engage in deliberative processes that both affect and are affected by context (Donaldson, 2019).…”
Section: Ei: ‘As Is’mentioning
confidence: 99%
“…Although most research has revealed and reified each construct’s importance in this regard, there are still some inconsistencies amongst findings. The most prevalent include an incomplete understanding of the impact that social norms have on influencing intentions (Heuer & Liñán, 2013), the fact that our intent does not always translate into action (Gielnik et al, 2014; Rauch & Hulsink, 2015; Shinnar et al, 2018), and finally questions remain over how differences in belief accessibility (and retrieval) could impact on intentional fluctuations (Broomé & Ohlsson, 2017; Meoli et al, 2019; Morris et al, 2012).…”
mentioning
confidence: 99%